Evolution and developmental expression of the sodium–iodide symporter (NIS, slc5a5) gene family: Implications for perchlorate toxicology. (7th July 2022) - Petersen, Ann M.; Small, Clayton M.; Yan, Yi‐Lin; Wilson, Catherine; Batzel, Peter; Bremiller, Ruth A.; Buck, C. Loren; von Hippel, Frank A.; Cresko, William A.; Postlethwait, John H.
Abstract: The vertebrate sodium–iodide symporter (NIS or SLC5A5) transports iodide into the thyroid follicular cells that synthesize thyroid hormone. The SLC5A protein family includes transporters of vitamins, minerals, and nutrients. Disruption of SLC5A5 function by perchlorate, a pervasive environmental contaminant, leads to human pathologies, especially hypothyroidism. Perchlorate also disrupts the sexual development of model animals, including threespine stickleback ( Gasterosteus aculeatus ) and zebrafish ( Danio rerio ), but the mechanism of action is unknown. To test the hypothesis that SLC5A5 paralogs are expressed in tissues necessary for the development of reproductive organs, and therefore are plausible candidates to mediate the effects of perchlorate on sexual development, we first investigated the evolutionary history of Slc5a paralogs to better understand potential functional trajectories of the gene family. We identified two clades of slc5a paralogs with respect to an outgroup of sodium/choline cotransporters ( slc5a7 ); these clades are the NIS clade of sodium/iodide and lactate cotransporters ( slc5a5, slc5a6, slc5a8, slc5a8, and slc5a12 ) and the SGLT clade of sodium/glucose cotransporters ( slc5a1, slc5a2, slc5a3, slc5a4, slc5a10, and slc5a11 ). We also characterized expression patterns of slc5a genes during development. Stickleback embryos and early larvae expressed NIS clade genes in connective tissue, cartilage, teeth, and thyroid. Stickleback males and females expressed slc5a5 and its paralogs in gonads. Single‐cell transcriptomics (scRNA‐seq) on zebrafish sex‐genotyped gonads revealed that NIS clade‐expressing cells included germ cells ( slc5a5, slc5a6a, and slc5a6b ) and gonadal soma cells ( slc5a8l ). These results are consistent with the hypothesis that perchlorate exerts its effects on sexual development by interacting with slc5a5 or its paralogs in reproductive tissues. These findings show novel expression domains of slc5 genes in stickleback and zebrafish, which suggest similar functions across vertebrates including humans, and provide candidates to mediate the effects of perchlorate on sexual development.